Plasticity of spatial hearing: behavioural effects of cortical inactivation. - Nodal, F; Bajo, V; King, A (2012)
The cerebral cortex plays a critical role in perception and in learning-induced plasticity. We show that reversibly silencing any of the main regions of auditory cortex impairs the ability of adult ferrets to localize sound, with the largest deficit seen after deactivating the primary fields. Although these animals had no trouble localizing longer sound bursts, their performance dropped considerably when auditory spatial cues were altered by occluding one ear with an earplug. In contrast to control ferrets, which recovered their localization abilities with intensive training, adaptation to an earplug was impaired following cortical inactivation, with the greatest disruption in plasticity observed after silencing higher-level cortical areas. These findings imply regional differences in the processing of spatial information across the auditory cortex.